Seasonal Variation of Hypericin and Pseudohypericin Contents in Hypericum Scabrum L. Growing Wild in Turkey - Ayan, Ali Kemal; Çırak, Cüneyt; Güney, Kerim (SAGE Publications, 2008)
The present study was conducted to determine ontogenetic and morphogenetic variations of hypericin and pseudohypericin contents in Hypericum scabrum growing in Turkey. Plants were harvested at vegetative, floral budding, full flowering, fresh fruiting and mature fruiting stages and observed for the presence of dark glands. Subsequently, they were dissected into stem, leaf and reproductive tissues, which were dried separately, and subsequently assayed for hypericin and pseudohypericin contents by HPLC. No hypericins were detected in stem tissues, while leaves and reproductive parts accumulated both compounds at different levels depending on growth stages. In general, higher levels of hypericin and pseudohypericin accumulation were observed in reproductive parts. Content of both hypericin forms decreased with advancing of plant development and reached their highest levels at floral budding stage.